Kajian Tentang Pembagian Harta Warisan Dari Suami Istri Yang Telah Meninggal Dunia Tanpa Keturunan Menurut Hukum Islam - Putri Samiat; Barzah Latupono; La Ode Angga (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Husband and wife who died left joint property both movable and immovable property where both husband and wife did not have children.Purposes of the Research: The goals to be achieved in this study are as follows: 1. To find out and analyze the division of inheritance of husband and wife who have died without offspring according to Islamic law. To find out and analyze the legal consequences if the inheritance of a husband and wife who has died without offspring is controlled by her husband's family according to Islamic law.Methods of the Research: This research is a type of normative legal research in which legal research whose object of study includes provisions of legislation and legal materials that are documentary, with the subject of Study on the Division of Inheritance From Husband and Wife Who Have Died According to Islamic Law.Results of the Research: The results obtained from this study are: 1. The division of inheritance of husband and wife who have died according to Islamic law, namely If referring to Article 179 compilation of Islamic Law (KHI) that is, if in marriage no child is born and the husband and wife has died and does not leave children and parents, then the right as heirs to the property of the husband and wife, namely the family of the husband and family on the part of the wife.The part that must be obtained by the husband's family and the wife's family when referring to Article 179 KHI is 1/2 part of the husband's family and 1/2 part of the wife's family. As a result of the law if the inheritance of the deceased husband and wife is controlled by the husband's family according to Islamic law, which is contrary to Article 97 KHI, where it is said that the inheritance of the deceased husband and wife must be divided by one-second (1/2) part for the family of the deceased Wife and one-second (1/2) part for the deceased husband's family.